Zinc oxide / titanium oxide composite photocatalyst and its preparation method and application in photodegradation of hydrogen sulfide

By curing the composite photocatalyst ZnO/TiO2 on porous fiber cotton and using ultraviolet light, the problem of difficult hydrogen sulfide removal in the prior art is solved, and efficient and green degradation effect is achieved, and the process is simple and no secondary pollute.

CN116037093BActive Publication Date: 2025-02-25FUZHOU UNIV
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202310062170.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-01-16
Publication Date
2025-02-25
Estimated Expiration
2043-01-16

AI Technical Summary

Technical Problem

The prior art is difficult to effectively remove the odorous toxic gas hydrogen sulfide, and the traditional methods have problems such as high cost, harsh reaction conditions, and possible secondary pollution.

Method used

The composite photocatalyst ZnO/TiO2 was prepared by solution-gel method, and it was cured on a sheet-shaped flexible porous fiber cotton, and hydrogen sulfide was degraded by ultraviolet light.

Benefits of technology

High-efficiency green degradation of hydrogen sulfide is achieved, with a degradation rate increased by 63.7%. The catalytic material sheet is simple to make, easy to operate, and no secondary pollution.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116037093B_ABST
    Figure CN116037093B_ABST
Patent Text Reader

Abstract

The present invention discloses a zinc oxide / titanium oxide (ZnO / TiO2) composite photocatalyst and a preparation method thereof, and a method for degrading hydrogen sulfide, a toxic gas with a foul odor, under light conditions. The carrier for the catalyst solidification is a flexible porous fiber cotton, and the photoreaction catalyst is a composite ZnO / TiO2 material that has been calcined at high temperature. In the photocatalytic experiment, the composite ZnO / TiO2 material is solidified on the flexible porous fiber cotton, and under ultraviolet light conditions, hydrogen sulfide can be completely degraded in a short time, and the cyclic treatment can be stable for a long time without failure, and hydrogen sulfide can be removed by mineralization and fixation as sulfate ions. This photocatalyst has broad application prospects in various spaces where hydrogen sulfide needs to be degraded, and the method for degrading hydrogen sulfide, a toxic gas with a foul odor, can bring huge potential economic and social effects.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of photocatalytic degradation of pollutants, and specifically relates to a zinc oxide / titanium oxide (ZnO / TiO2) composite photocatalyst and a preparation method thereof, and an application thereof in degrading malodorous toxic gas hydrogen sulfide under light conditions. Background Art

[0002] Hydrogen sulfide is a typical sulfur-containing inorganic malodorous gas pollutant and a byproduct released in many production processes, such as acid gas combustion, petroleum refining, papermaking or wastewater treatment. Low concentrations of hydrogen sulfide can cause tears, nausea, headaches, chest tightness, etc., while high concentrations can cause coma, respiratory failure and even death. At the same time, hydrogen sulfide can seriously corrode metal parts of manufacturing facilities, causing a great impact on industrial production. In addition, H2S can also be converted into SO in the atmosphere. x Pollutants such as H2S and SO x It will lead to extreme weather such as acid rain and cause the deterioration of the ecological environment. Hydrogen sulfide will not only corrode equipment and pipelines, cause environmental pollution, but also seriously threaten personal safety. H2S is highly toxic, almost as toxic as hydrogen cyanide, and several times more toxic than carbon monoxide. In addition, H2S is widely distributed and exists in common work and life scenes. Long-term work and life in an environment with H2S will cause irreversible physical damage to the human body. Therefore, how to effectively remove hydrogen sulfide is an urgent problem to be solved.

[0003] Traditional methods for treating the malodorous gas hydrogen sulfide have certain limitations. In recent years, many new deodorization methods have emerged. Among them, photocatalytic degradation of hydrogen sulfide has the advantages of high treatment efficiency, mild reaction conditions, and no secondary pollution, so it has received more and more attention. TiO2 has been widely used in many fields due to its advantages such as high chemical stability, low toxicity and low cost, especially in the field of photocatalytic environmental applications. However, how to improve the quantum efficiency of TiO2 remains a major challenge, because most of the electrons and holes formed by light are recombined without participating in the redox reaction, which inhibits the quantum yield. Adding a small amount of ZnO to TiO2 can reduce the particle size of TiO2. The addition of ZnO also inhibits the phase transition of TiO2 from anatase to rutile, thereby improving the thermal stability of the catalyst. Summary of the invention

[0004] The purpose of the present invention is to solidify the composite photocatalyst ZnO / TiO2 on a sheet of flexible porous fiber cotton, and use ultraviolet light irradiation to achieve efficient and green degradation of the odorous toxic gas hydrogen sulfide. The present invention has mild conditions, simple preparation of the catalytic material sheet, excellent treatment performance, and has broad practical value and application research prospects.

[0005] To achieve the above-mentioned object of the invention, the present invention is implemented by the following technical solutions:

[0006] A composite photocatalyst ZnO / TiO2 is synthesized, and a method for using the material to degrade odorous toxic gas hydrogen sulfide under light conditions: the composite photocatalyst ZnO / TiO2 is solidified on a porous fiber carrier and placed in a purifier device containing an ultraviolet lamp tube, and the purifier device is placed 3m 3 After the environmental evaluation cabin is set to a constant temperature and humidity, hydrogen sulfide is introduced into the cabin, and then the purifier device is turned on to degrade the hydrogen sulfide.

[0007] More specifically:

[0008] A synthesis of a composite photocatalyst ZnO / TiO2 and a method for degrading odorous toxic gas hydrogen sulfide under light conditions using the material, the specific steps are:

[0009] (1) Preparation of composite photocatalyst ZnO / TiO2

[0010] Using tetrabutyl titanate and zinc acetate as precursors, ZnO / TiO2 photocatalyst was prepared by solution-gel method. First, a certain amount of ethanol was measured, and then an appropriate amount of tetrabutyl titanate and zinc acetate (the mass ratio of ZnO to TiO2 was 5-20%) was added, which was recorded as solution A; deionized water, anhydrous ethanol and glacial acetic acid were stirred and mixed in a volume ratio of 3:20:1 to obtain solution B. Solution B was stirred continuously in an ice water bath, and when the temperature of the solution in the beaker dropped to 0℃, solution A was slowly dripped into it and stirred until a sol was formed. Stirring was continued for 2h, and then the obtained gel was dried in an oven at 80-100℃ for 8-12h, and then the dried sample was ground into powder and calcined at 300-500℃ in a muffle furnace in a clean air atmosphere for 6-8h, with a heating rate of 2-5℃ / min.

[0011] (2) Preparation of catalytic material sheets

[0012] The photocatalyst ZnO / TiO2 ground to a fine enough size is stirred with the titanium colloid solution in a certain proportion, and the stirred suspension is vaporized in a high-pressure spray gun, and then sprayed evenly on the surface of the sheet-like flexible porous fiber cotton. The sprayed flexible porous fiber cotton is placed in a muffle furnace, and then heated to 300-500 ℃ at a heating rate of 2-5 ℃ / min, and kept warm for 8-12 hours. The muffle furnace is closed, and when the temperature drops to room temperature, the catalytic material sheet is taken out and placed in a dry sealed bag for use.

[0013] (3) Degradation of pollutants

[0014] Place the solidified catalytic material sheet in the purifier device, and then place the purifier device in a 3 m 3In the closed environmental evaluation cabin, after the temperature and humidity are maintained at a constant level, a certain amount of hydrogen sulfide is introduced into the cabin. The agitator in the cabin is turned on to mix the hydrogen sulfide evenly. The concentration of hydrogen sulfide in the cabin is observed through the hydrogen sulfide detector. When the concentration of polluted gas in the cabin is stable, the purifier device is turned on to degrade the hydrogen sulfide.

[0015] The advantages of the present invention are:

[0016] 1) The present invention uses a composite photocatalyst ZnO / TiO2, which has good photocatalytic activity and is green and pollution-free;

[0017] 2) The present invention can completely degrade the odorous and toxic gas hydrogen sulfide in a short time;

[0018] 3) The present invention adopts ultraviolet light irradiation, the reaction cost is low, and the reaction conditions are simple and mild;

[0019] 4) The catalytic material sheet of the present invention has a simple manufacturing process, a simple and easy operation method, and has broad application prospects. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] Figure 1 The performance diagram of hydrogen sulfide degradation of ZnO / TiO2 photocatalytic materials with different mass ratios;

[0021] Figure 2 This is a graph showing the durability and stability of the ZnO / TiO2 photocatalytic material's performance in degrading hydrogen sulfide;

[0022] Figure 3 This is the scanning electron microscope (SEM) image of the composite photocatalyst ZnO / TiO2;

[0023] Figure 4 This is the XRD pattern of the composite photocatalyst ZnO / TiO2;

[0024] Figure 5 This is the UV-Vis absorption spectrum of the composite photocatalyst ZnO / TiO2;

[0025] Figure 6 This is the nitrogen isothermal absorption / desorption curve of the composite photocatalyst ZnO / TiO2. DETAILED DESCRIPTION

[0026] The following examples further illustrate the present invention. Figure 1 shown.

[0027] Example 1

[0028] A synthesis of a composite photocatalyst ZnO / TiO2 and a method for degrading odorous toxic gas hydrogen sulfide under light conditions using the material, the specific steps are:

[0029] (1) Using tetrabutyl titanate and zinc acetate as precursors, ZnO / TiO2 photocatalysts were prepared by the solution-gel method. First, a certain amount of ethanol was measured, and then an appropriate amount of tetrabutyl titanate and zinc acetate (the mass ratio of ZnO to TiO2 was 15%) was added, which was recorded as solution A; deionized water, anhydrous ethanol and glacial acetic acid were stirred and mixed in a volume ratio of 3:20:1 to obtain solution B. Solution B was stirred continuously in an ice water bath, and when the temperature of the solution in the beaker dropped to 0℃, solution A was slowly dripped into it and stirred until a sol was formed. Stirring was continued for 2h, and then the obtained gel was dried in an oven at 100℃ for 12h, and then the dried sample was ground into powder and calcined at 500℃ in a muffle furnace in a clean air atmosphere for 8h, with a heating rate of 5℃ / min.

[0030] (2) Weigh a certain mass of ZnO / TiO2 photocatalyst and place it in a beaker. Add it to 800 mL of titanium colloid solution and stir for 12 h to form a suspension. Then use the spraying method to spray 200 mL of the high-pressure spray gun evenly on the surface of the substrate material, then place it in a 100 °C oven for drying and take it out. Repeat the spraying 4 times. Finally, place the catalytic material sheet in a muffle furnace and heat it to 500 °C for 8 h. After cooling naturally, take it out to obtain the catalytic material sheet.

[0031] (3) The solidified sheet-like flexible porous fiber cotton is placed in parallel stacking between the lamps in the photocatalytic reactor. There are three ultraviolet lamps with a wavelength of 254nm and a power of 8W in the reactor. The shell and the reaction chamber are made of magnesium-aluminum alloy. Then the device is placed on an operating platform rack with a height of 1m in the closed environment evaluation cabin, and the constant temperature and humidity function of the closed environment evaluation cabin is turned on. After the temperature and humidity are stable, open the air inlet valve of the closed environment evaluation cabin and open the pressure reducing valve of the standard pollutant cylinder. When the pollutant concentration reaches the set value of 5-5.5ppm, turn on the photocatalytic reactor and start the pollutant removal test.

[0032] (4) When the detector reading drops to zero, record the test data, turn off the photocatalytic reactor, and the pollutant removal process is completed. Open the exhaust system of the closed evaluation chamber to fully replace the atmosphere in the closed evaluation chamber, and the test is completed.

[0033] Example 2

[0034] The specific experimental method is basically the same as that of Example 1 in this section, except that the mass ratio of ZnO to TiO2 is 10%.

[0035] Example 3

[0036] The specific experimental method is basically the same as that of Example 1 in this section, except that the mass ratio of ZnO to TiO2 is 20%.

[0037] Example 4

[0038] The specific experimental method is basically the same as Example 1 of this section, except that the photocatalyst is TiO2 without ZnO doping.

[0039] like Figure 1 As shown in the figure, after turning on the light, for H2S with an initial concentration of 5.5 ppm, the TiO2 photocatalyst alone needs 370 minutes to complete the degradation of hydrogen sulfide, and the degradation rate is 0.0447 mL / min. Under the same conditions, the photocatalytic degradation rate of hydrogen sulfide by the modified ZnO / TiO2 photocatalyst increases first and then decreases with the increase of ZnO content. Among them, the 15% ZnO / TiO2 photocatalyst has the best performance, and it only takes 220 minutes to achieve complete degradation of H2S (conversion rate reaches 99.9%), and the degradation rate is 0.073 mL / min. Its catalytic rate is 63.7% higher than that of TiO2. The 15% ZnO / TiO2 photocatalyst has the best degradation effect on hydrogen sulfide, which may be due to the fact that the appropriate amount of ZnO doping increases the specific surface area of ​​the catalyst, reduces the grain size, exposes more catalytic centers, and changes the acid-base properties of the photocatalyst surface, thereby improving the photocatalytic degradation rate of hydrogen sulfide.

[0040] like Figure 2 As shown in the figure, in the first cycle experiment, the degradation of hydrogen sulfide can be completed in 210 minutes, and the degradation rate is 0.075 mL / min. The tenth cycle experiment requires 280 minutes to complete the degradation of hydrogen sulfide, and the degradation rate is 0.057 mL / min, which is a decrease of 24.0%. It took a total of 2320 minutes to complete the 10 experiments. During this period, 160.75 mL of hydrogen sulfide was removed, and the average degradation rate was 0.069 mL / min. The degradation rate of hydrogen sulfide can still reach 99.9%. It can be seen that the prepared ZnO / TiO2 photocatalyst material has excellent photocatalytic stability and durability for hydrogen sulfide.

[0041] like Figure 3 As shown, undoped TiO2( Figure 3 -a) The photocatalyst is irregularly spherical and has a large particle size. When ZnO is doped ( Figure 3 -bf), with the increase of ZnO co-doping amount, the size of ZnO / TiO2 spherical nanoparticles gradually decreases. The above results indicate that the size of ZnO / TiO2 photocatalyst is smaller than that of intrinsic TiO2.

[0042] like Figure 4As shown in the figure, the diffraction peak of intrinsic TiO2 has a distinct peak and high intensity, indicating that the intrinsic TiO2 has a high degree of crystallinity and a large particle size. With the increase of the ZnO doping ratio, the half-height width of the characteristic diffraction peak of the sample gradually increases, and the peak intensity gradually decreases, indicating that ZnO doped into the TiO2 lattice will lead to a decrease in the crystallinity and grain size of the ZnO / TiO2 heterojunction photocatalyst.

[0043] like Figure 5 As shown in the figure, the absorption band edge of intrinsic TiO2 is 370 nm, and there is a slight red shift after loading ZnO. ZnO / TiO2 photocatalyst samples with different ratios have strong light absorption in the range of 200 nm-370 nm, and almost no absorption peak in the visible light range, which shows that this type of catalyst has a good light response in the ultraviolet light range.

[0044] like Figure 6 As shown, it can be seen that all ZnO / TiO2 photocatalysts have higher specific surface areas than TiO2, among which 15% ZnO / TiO2 has the largest specific surface area, which is 2.38 times and 3.45 times that of TiO2 and ZnO respectively. Compared with pure TiO2, the specific surface area of ​​ZnO / TiO2 composite materials is greatly improved.

[0045] The above description is only a preferred embodiment of the present invention. All equivalent changes and modifications made according to the scope of the patent application of the present invention should fall within the scope of the present invention.

Claims

1. Application of a zinc oxide / titanium oxide composite photocatalyst in photodegradation of hydrogen sulfide, characterized in that: The zinc oxide / titanium oxide composite photocatalyst is solidified on a porous fiber carrier, and then hydrogen sulfide is degraded under light irradiation, where the light source is ultraviolet light; The preparation method of the zinc oxide / titanium oxide composite photocatalyst specifically comprises the following steps: taking ethanol, tetrabutyl titanate and zinc acetate to mix to obtain solution A, then stirring and mixing deionized water, anhydrous ethanol and glacial acetic acid in a volume ratio of 3:20:1 to obtain solution B, dripping solution A into solution B in an ice water bath and stirring until a sol is formed, then drying the obtained gel at 80-100°C for 8-12 h, and grinding it into powder, and finally calcining at 300-500°C in an air atmosphere for 6-8 h, with a heating rate of 2-5°C / min, to obtain a zinc oxide / titanium oxide composite photocatalyst, namely a ZnO / TiO2 composite photocatalyst; the mass ratio of zinc oxide to titanium oxide in the composite photocatalyst is 5-20%.

2. The use according to claim 1, characterized in that: The specific steps of curing the zinc oxide / titanium oxide composite photocatalyst on the porous fiber carrier are as follows: (1) Pre-preparation of flexible porous fiber cotton for curing zinc oxide / titanium oxide composite photocatalyst: Mix and stir the zinc oxide / titanium oxide composite photocatalyst and titanium colloid solution, vaporize the stirred suspension in a high-pressure spray gun, and evenly spray it on the surface of the sheet-like flexible porous fiber cotton; (2) High-temperature calcination of catalytic materials: The sprayed flexible porous fiber cotton is placed in a muffle furnace, and then heated to 300-500 °C at a heating rate of 2-5 °C / min and kept at this temperature for 8-12 h to obtain a flexible porous fiber cotton cured with zinc oxide / titanium oxide composite photocatalyst.

3. The use according to claim 2, characterized in that: A titanium colloid solution was used as a binder, and the mass ratio of the titanium colloid solution to the zinc oxide / titanium oxide composite photocatalyst was 160:1.

Citation Information

Patent Citations

  • Hydroxyl oxidize iron modified titanium dioxide composite photocatalyst as well as preparation method and application thereof

    CN108970613A